2017
DOI: 10.1177/0961203316689145
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of neuropsychiatric events in systemic lupus erythematosus based on clinical phenotypes; prospective data from the Leiden NP SLE cohort

Abstract: Objective The objective of this study was to assess whether clinical and patient's reported outcomes are associated with a different pathophysiological origin of neuropsychiatric events presenting in systemic lupus erythematosus. Methods A total of 232 neuropsychiatric events presenting in 131 systemic lupus erythematosus patients were included. Neuropsychiatric systemic lupus erythematosus diagnosis was established per event by multidisciplinary evaluation. All neuropsychiatric events were divided according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
1
14
0
1
Order By: Relevance
“…NP events are associated with a significant negative impact on patient‐reported health‐related quality of life (HRQoL), regardless of attribution and adjusting for global SLE disease activity, cumulative organ damage, and medications . Thus, all NP events are of clinical significance, but the treatment pathway is dependent on the correct attribution.…”
Section: Current Status Of Npslementioning
confidence: 99%
See 1 more Smart Citation
“…NP events are associated with a significant negative impact on patient‐reported health‐related quality of life (HRQoL), regardless of attribution and adjusting for global SLE disease activity, cumulative organ damage, and medications . Thus, all NP events are of clinical significance, but the treatment pathway is dependent on the correct attribution.…”
Section: Current Status Of Npslementioning
confidence: 99%
“…Given the paucity of clinical trials in NPSLE, information on treatment and outcomes is derived from observational studies and extrapolated from experience with other organ system disease in SLE and related disorders. Short‐term and long‐term outcomes of NP events are generally favorable, particularly for NP events attributed to SLE .…”
Section: Current Status Of Npslementioning
confidence: 99%
“…It is reported that infection, lupus nephritis, hematological abnormality, NPSLE, and interstitial pneumonia are top causes of deaths in China (23). The two recognized underlying mechanisms of the immunopathogenesis of NPSLE were ischemic and inflammatory mechanisms, including blood-brain barrier dysfunction and production of pro-inflammatory cytokines which mediated by autoantibody (5,24). However, NPSLE pathogenesis is incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the study, a varying number of SLE sufferers (from 15% to 75%) present with neuropsychiatric (NP) symptoms that cover the whole spectrum of psychiatric dysfunction [ 9 , 10 ]. These NP manifestations are associated with a reduced quality of life [ 11 , 12 , 13 ] and, when severe, they substantially contribute to the morbidity and mortality rates of SLE patients [ 14 ]. Nowadays, the etiology of NPSLE remains poorly understood, as is also the case for SLE and most autoimmune diseases.…”
Section: Systemic and Np Aspects Of Lupus Diseasementioning
confidence: 99%